Answer : The an explicit formula for the arithmetic sequence will be,
![a(n)=a-18* (n-1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/t9z29p0twbiw8k344eivehegiqusbntyo5.png)
Step-by-step explanation :
Arithmetic progression : It is a sequence of numbers in which the difference of any two successive number is a constant.
The general formula of arithmetic progression is:
![a(n)=a+(n-1)d](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vvzkocfq4l10d1k1gu82vux3g9mazk21lz.png)
where,
a(n) = nth term in the sequence
a = first term in the sequence
d = common difference
n = number of terms in the sequence
As we are given that:
Common difference = d = -18
Thus, the formula of arithmetic progression will be:
![a(n)=a+(n-1)d](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vvzkocfq4l10d1k1gu82vux3g9mazk21lz.png)
![a(n)=a+(n-1)* (-18)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tpgk95emzwa092yr0khjlg5nl2r411n9uk.png)
![a(n)=a-18* (n-1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/t9z29p0twbiw8k344eivehegiqusbntyo5.png)
For example:
Let n=1 :
![a(n)=a-18* (n-1)\\\\a(1)=a-18(1-1)=a](https://img.qammunity.org/2019/formulas/mathematics/middle-school/lb1c8xvuelsya6pcc38x0llh76nletg739.png)
Let n=2 :
![a(n)=a-18* (n-1)\\\\a(2)=a-18(2-1)=a-18](https://img.qammunity.org/2019/formulas/mathematics/middle-school/en1q0nc1ld2w87m5jlyyopm7ofcpuac35s.png)
Let n=3 :
![a(n)=a-18* (n-1)\\\\a(3)=a-18(3-1)=a-36](https://img.qammunity.org/2019/formulas/mathematics/middle-school/v8la6krv9b7dy0qavkcffrw2a050eccc2w.png)
The sequence will be, a, (a-18), (a-36),.........
Thus, the an explicit formula for the arithmetic sequence will be,
![a(n)=a-18* (n-1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/t9z29p0twbiw8k344eivehegiqusbntyo5.png)